Malic acid production by chemically induced Aspergillus niger MTCC 281 mutant from crude glycerol. (March 2018) - Iyyappan, J.; Bharathiraja, B.; Baskar, G.; Jayamuthunagai, J.; Barathkumar, S.; Anna shiny, R.
Highlights: Malic acid is a C4 dicarboxylic acid with many food and beverage industry applications. Methanol and malic acid resistant Aspergillus niger MTCC281 mutant was generated. Crude glycerol served as substrate for malic acid production without any pretreatment. Enhanced production of malic acid was achieved during co-fermentation with glucose. Maximum malic acid titer was 77.38 g/L from crude glycerol. Abstract: In the present investigation, crude glycerol derived from transesterification process was utilized to produce the commercially-valuable malic acid. A combined resistant on methanol and malic acid strain of Aspergillus niger MTCC 281 mutant was generated in solid medium containing methanol (1–5%) and malic acid (40–80 g/L) by the adaptation process for 22 weeks. The ability of induced Aspergillus niger MTCC 281 mutant to utilize crude glycerol and pure glycerol to produce malic acid was studied. The yield of malic acid was increased with 4.45 folds compared with that of parent strain from crude glycerol. The highest concentration of malic acid from crude glycerol by using beneficial mutant was found to be 77.38 ± 0.51 g/L after 192 h at 25 °C. This present study specified that crude glycerol by-product from biodiesel production could be used for producing high amount of malic acid without any pretreatment.